Procurement and circulation of obsidian in the province of La Pampa, Argentina - Beron, Monica Alejandra (2018)
The goal of this study is to report the progress regarding the procurement and circulation of obsidian by hunter-gatherer populations during the Late Holocene in the province of La Pampa, Argentina. Twenty five samples were analysed in two stages; in the first stage neutron activation analysis (INAA) was used, while X-ray fluorescence (XRF) was employed in the second stage. This paper adds nine archaeological samples from new sites and one from the Lihué Calel obsidian source, unknown so far. The results allow us to consider the sourcing of the obsidian, which was found in archaeological sites from four research areas located in the south and east of the province. The results generated in this new stage are integrated with those previously obtained and discussed in relation to information provided by other researchers in the region. They indicate that the obsidian recovered was procured from Andean and extra Andean sources located in the Argentine provinces of Neuquén and Mendoza. New data expands the spatial perspective of our interpretations to four new research areas: Curacó basin, Lihué Calel hills, Valles Transversales (Transversal Valleys) and Bajos sin Salida (Endorheic low areas). The origin of the obsidian at La Pampa sites adds to another cluster of archaeological evidence showing strong long distance interactions that existed between hunter-gatherer societies that inhabited the central region of Argentina in the late Holocene. Access to secondary deposits could have also contributed to source variability.